Поняття «метатекстуальність» і «метаоповідь» у літературознавчому дискурсі - Ватажко, Е. (Слово і Час, 2022)
Статтю присвячено теорії метатексту / метатекстуальності, співвідношенню метатексту і метаоповіді й висвітленню основних концепцій,
що стосуються цих понять у сучасному літературознавстві. Терміни
«метатекст» та «метаоповідь» / «метапроза» з’явилися майже одночасно в західній науці та базуються на дискурсивній практиці літератури
кінця ХХ ст. Термін «метатекст», створений за аналогією до поняття
«метамова», виник у рамках наратології і пов’язаний зі структуралістською теорією. Метатекстові елементи стосуються аналізу стилів,
жанрів і типів висловлювання, дискурсивних функцій тощо. Натомість
термін «метаоповідь» має очевидний зв’язок із теорією жанрів й актуалізується у контексті епохи постмодернізму. У статті стверджується, що метатекстуальність пов’язана з метакритикою та структурними особливостями тексту або висловлювання, а метапрозові явища варто розглядати на базі постмодерністської теорії як особливий вид тексту, що
набуває поширення в художній літературі сучасності. Увагу акцентовано
на появі та розвитку метадискурсу в культурній та науковій свідомості другої половини ХХ ст. Undoubtedly, the second half of the 20th century and the early 21st century are notable for
the extensive artistic experiment, including metatextual and metafictional phenomena. Such
scholars as Gérard Genette, Anna Wierzbicka, Patricia Waugh, Linda Hutcheon, Robert
Sholes, and many others focused on the mentioned issues in their research work. Therefore,
this paper considers metatextuality and metafiction in the theoretical perspective tracing
the origins of metatextuality and its connections with postmodern literature. The terms
‘metatext’ and ‘metafiction’ appeared as rather close in time. Notably, both of them are based
on the discursive practices of the late 20th century. However, the term ‘metatext’ originated
in the scholarly practice of structuralism. It is obvious that ‘metatext’ was constructed by
analogy with the concept of ‘metalanguage’. Either of them does not exist without the initial
text (or language). Metatextual elements are important for analyzing styles, genres, types of
expression, discursive functions, and more. On the other hand, the term ‘metafiction’ has
an obvious connection with genre studies. Metafiction qualifies as a special kind of literary
text that became characteristic of the postmodern era. Such features as self-referentiality of
artistic expression, introspection, and self-consciousness became essential for postmodern
aesthetics. Metatextuality relates to the narrative theory and metacritiсism, while
metafictionality is applicable within the intertextual analysis. Th us, the paper highlights an
advance of metadiscourse in the cultural consciousness of the late 20th century.